Hypoxia-regulated microRNAs in human cancer - Shen Guomin; Li Xiaobo; Jia Yong-feng; Piazza Gary A; Xi Yaguang (Acta Pharmacologica Sinica, 2016)
Guomin SHEN1, Xiaobo LI1, Yong-feng JIA2, Gary A PIAZZA1, Yaguang XI1, * 1Mitchell Cancer Institute, University of South Alabama, Alabama, USA; 2Inner Mongolia Medical University, Hohhot 010021, China Hypoxia plays an important role in the tumor microenvironment by allowing the development and maintenance of cancer cells, but the regulatory mechanisms by which tumor cells adapt to hypoxic conditions are not yet well understood. MicroRNAs are recognized as a new class of master regulators that control gene expression and are responsible for many normal and pathological cellular processes. Studies have shown that hypoxia inducible factor 1 (HIF1) regulates a panel of microRNAs, whereas some of microRNAs target HIF1. The interaction between microRNAs and HIF1 can account for many vital events relevant to tumorigenesis, such as angiogenesis, metabolism, apoptosis, cell cycle regulation, proliferation, metastasis, and resistance to anticancer therapy. This review will summarize recent findings on the roles of hypoxia and microRNAs in human cancer and illustrate the machinery by which microRNAs interact with hypoxia in tumor cells. It is expected to update our knowledge about the regulatory roles of microRNAs in regulating tumor microenvironments and thus benefit the development of new anticancer drugs. Keywords: microRNA; hypoxia; HIF1; human cancer; angiogenesis; apoptosis; cell cycle; cancer metastasis; chemoresistance; radioresistance This study is supported by the NIH/NCI grant 1R21CA160280-01A1 (Yaguang XI). We sincerely convey our apology to the colleagues who have greatly contributed to this field but whose publications were not cited in this review due to limitations of time and space. * To whom correspondence should be addressed. E-mail xi@usouthal.edu Received 2012-11-22 Accepted 2012-12-24